2021
DOI: 10.1111/vcp.13024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of predicted ionized calcium in dogs with total hypercalcemia and total hypocalcemia

Abstract: Background: Abnormal total calcium (tCa) values do not necessarily imply dysregulated ionized calcium. Objectives:We aimed to evaluate the diagnostic performance of predicted ionized calcium (piCa) regarding true calcium status in dogs with abnormal tCa. Methods:This was a cross-sectional multicenter study. piCa and its prediction interval (PI) were calculated in 114 dogs, from three different hospitals, with either increased (62) or decreased tCa (52), All dogs also had ionized calcium and a biochemical profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In that study, the discordance between hypercalcaemia classified by total versus ionized calcium in non-hyperphosphataemic patients was 34.1% (Lebastard et al, 2021). Therefore, the current study could have underestimated or overestimated the number of dogs that were truly hypercalcaemic.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In that study, the discordance between hypercalcaemia classified by total versus ionized calcium in non-hyperphosphataemic patients was 34.1% (Lebastard et al, 2021). Therefore, the current study could have underestimated or overestimated the number of dogs that were truly hypercalcaemic.…”
Section: Discussionmentioning
confidence: 61%
“…It has been previously reported that using total calcium to predict elevated ionized calcium may lead to an overestimation of normocalcaemia (Schenck & Chew, 2005). However, a more recent study demonstrated that total calcium may lead to an overestimation of elevated ionized calcium (Lebastard et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, these authors recommend the evaluation of iCa in plasma as a more accurate predictor of blood Ca status in dairy cattle. In addition, in other species such as dogs (Lebastard et al, 2021) and humans (Papadopoulou et al, 2021;Yu and Sharma 2022), the evaluation of calcemia to establish proper treatment strategies in patients under hospital settings is consistently centered on iCa instead of tCa. Nevertheless, most studies dealing with hypocalcemia in dairy cattle report tCa concentrations, possibly due to the complexity of blood sample processing and the higher cost of laboratory analysis for iCa.…”
Section: Discussionmentioning
confidence: 99%